Using of calculated neutron multiplicities for determination of the excitation energy of fission fragments - Bezshyyko, O.A.; Golinka-Bezshyyko, L.O.; Kadenko, I.M.; Dzhygadlo, R.S. (Вопросы атомной науки и техники, 2007)
Study of excitation energy distribution of fission fragments as a function of its mass and charge is important for investigation of the fission process mechanism and useful for various applications. Direct measurement of excitation energy of primary fission fragments (before escape of neutrons) is very problematical. Method to obtain these excitation energies is considered using calculated neutron multiplicities and experimental values of differential yields of fragments pairs after emission of neutrons. We used code Empire II to calculate neutron multiplicities depending on various characteristics of nuclear structure, fission process and de-excitation of the fission fragments. Дослідження розподілу енергії збудження уламків поділу як функції їх маси та заряду може надати важливу інформацію про механізми процесу поділу та може бути корисним для вирішення цілого ряду прикладних задач. Пряме експериментальне визначення енергії збудження уламків поділу зіштовхується з цілим рядом проблем різного характеру. Розглянуто підхід для визначення енергії збудження уламків з використанням розрахованих множинностей нейтронів та експериментальних величин диференційних виходів пар уламків після вильоту з них нейтронів. Для розрахунків множинностей нейтронів використовувався програмний код Empire II. Изучение распределения энергии возбуждения осколков деления как функции массы и заряда осколков может дать важную информацию о механизмах процесса деления и быть полезным для целого ряда приложений. Прямое экспериментальное определение энергии возбуждения осколков деления сталкивается с целым рядом проблем различного характера. Рассмотрен подход для определения энергии возбуждения осколков деления с использованием рассчитанных множественностей нейтронов и экспериментальных величин дифференциальных выходов пар осколков после вылета из них нейтронов. Для расчетов множественностей нейтронов использовался программный код Empire II.